Desenvolvimento de scaffolds condutivos de PLA e PVA com PEDOT para engenharia de tecidos - Rodrigues, Tayná Copes (Universidade do Vale do Rio dos Sinos, 2023)
In the area of regenerative medicine, multidisciplinary knowledge has been applied to build functional tissues and organs, aiming to prolong the quality and duration of life. One of the methods used for the development of these tissues is the incorporation of cells in scaffolds. The scaffold material must be biodegradable and bioabsorbable, in addition to having electrical conductivity to improve cell-to-cell communication. Thus, among the main materials used for the development of scaffolds, biodegradable polymers such as poly (lactic acid) PLA, poly (vinyl alcohol) PVA, alginate and conductive polymers such as PEDOT:PSS. The aim of this study was the development of scaffolds with conductive characteristics based on PLA or PVA and PEDOT as conductive element. For this, the chemical synthesis of the PEDOT:PSS was first performed, evaluating the method of obtaining and characteristics obtained, in addition to the possibility of substituting PSS for alginate. Subsequently, PEDOT:PSS was added to PLA and PVA with glycerol solutions. Then, scaffolds were produced through the method of molding with five different compositions of PLA, PVA and PEDOT:PSS. The scaffolds were characterized by Fourier transform infrared spectrometry, differential scanning calorimetry, thermogravimetric analysis, compression test, resistivity measurement by the four-point method, water absorption capacity, degradation assay and, cell viability. It was not possible to substitute PSS for alginate using the same methodology. Thermally stable scaffolds were produced, with porosity in the range of 75 – 96%, with appropriate rigidity for different types of human tissues, and with water absorption capacity ranging from 567% for scaffolds based on PVA and PEDOT:PSS at 26.5% for PLA with 10% PEDOT:PSS. The PVA scaffolds with PEDOT:PSS showed a conductivity of 8.9 x 10-4 ± 6.6 x 10-4 S/cm, and the PLA scaffolds 2.7 x 10-6 ± 9.7 x 10-6 S/cm for 10% PEDOT:PSS, sufficient to encourage cell proliferation and differentiation. PLA scaffolds with 10% PEDOT:PSS did not show cytotoxicity when compared to conventional 2D culture in plates, while the others scaffolds tested showed lower cell viability. Thus, the 10% PLA scaffold is most suitable for tissue engineering applications.
Keywords: Scaffolds; PLA; PVA; PEDOT; Engenharia de tecidos; Tissue engineering; ACCNPQ::Engenharias::Engenharia Elétrica